Analysis of Factors Influencing the Participation of Husbands of Reproductive-Age Couples as Family Planning (FP) Acceptors: A Literature Review - Zuhro, Andina Fatimatus; Sari, Jayanti Dian Eka; Rachma, Erica Feby; Bakar, Norasma; Islam, Khandaker Fadwana (Health Dynamics, 2025)
The participation of husbands in the Family Planning (FP) program is very low even though their role is very important in realizing a prosperous family. The low participation of husbands as FP acceptors is influenced by the limited choice of contraceptives for men and the lack of awareness of the importance of a shared role in reproductive health. The purpose of this study was to identify various factors that influence the participation of husbands as acceptors of the Family Planning (FP) program. This study used the method Systematic Literature Review as its main strategy by searching articles through Google Scholar and ScienceDirect. Based on the results of the search and analysis, seven relevant articles were found and worthy of being used as review material in this research literature review. The review of seven articles showed that husbands’ participation as family planning acceptors was most consistently influenced by knowledge, wife’s support, health workers’ roles, attitudes, and family income. However, other factors such as education, employment, and sources of information show varying results.